2018
DOI: 10.3847/2041-8213/aab9aa
|View full text |Cite
|
Sign up to set email alerts
|

Non-LTE Calculations of the Fe i 6173 Å Line in a Flaring Atmosphere

Abstract: The Fe I 6173 Å line is widely used in the measurements of vector magnetic fields by instruments including the Helioseismic and Magnetic Imager (HMI). We perform non-local thermodynamic equilibrium calculations of this line based on radiative hydrodynamic simulations in a flaring atmosphere. We employ both a quiet-Sun atmosphere and a penumbral atmosphere as the initial one in our simulations. We find that, in the quiet-Sun atmosphere, the line center is obviously enhanced during an intermediate flare. The enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…The measured magnetic field strength then decreases at an early period since the flare heating increases the formation height of the line. Such a result is similar to other lines that are used for magnetic field measurement, including the Ni I 6768 Å line (Ding et al 2002), and the Fe I 6173 Å line (Hong et al 2018).…”
Section: Magnetic Field Inversionsupporting
confidence: 81%
See 2 more Smart Citations
“…The measured magnetic field strength then decreases at an early period since the flare heating increases the formation height of the line. Such a result is similar to other lines that are used for magnetic field measurement, including the Ni I 6768 Å line (Ding et al 2002), and the Fe I 6173 Å line (Hong et al 2018).…”
Section: Magnetic Field Inversionsupporting
confidence: 81%
“…The height where τ = 1 is about 360 km for the line center, and 200 km for the absorption trough. The formation height of the absorption trough is somehow similar to that of the Fe I 6173 Å line center (Hong et al 2018). The line source function is defined as…”
Section: Model F10mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (1989) [47]. Some study with Stokes parameters of spectral lines can be found (Hong et al(2018) [91]). Due to the distortion of the spectral lines with the variation of solar atmosphere in the solar eruptive process [3], the analysis of relevant Stokes parameters of the spectral lines is a notable topic.…”
Section: Discussion For Some New Challenges On Measurements Of Solarmentioning
confidence: 99%
“…Non-LTE9 modeling by Hong et al. (2018) explained the profile changes of Fe I 6173 Å line that the HMI uses and provided a quantitative assessment of magnetic transients. Song et al.…”
Section: Rapid Changes Of Magnetic Fields Associated With Flaresmentioning
confidence: 99%